The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2528/pierm18123101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Detailed Design of Unequal-Split 3-Way Bagley Power Dividers Using Uniform Transmission Lines

Abstract: In this paper, we systematically derive design equations for 3-way Bagley power dividers with arbitrary split ratios using interconnecting transmission lines with the same characteristic impedance. The exact value of the characteristic impedance for a specific dividing ratio is determined using these equations to achieve perfect input port matching. To validate the design procedure, two microstrip dividers with different split ratios, 1 : 3 : 1 and 1 : 10 : 1, are designed, simulated, fabricated, and measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Therefore, the positive square root for both y 1 and y 4 are used to derive both Z 1 and Z 4 in Equations (22) and (30), respectively. On the other hand, the negative square root for both y 2 and y 3 are used to derive both Z 2 and Z 3 in Equations (25) and 28, respectively. All of this is shown in Equations (31)- (34).…”
Section: S 51 Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the positive square root for both y 1 and y 4 are used to derive both Z 1 and Z 4 in Equations (22) and (30), respectively. On the other hand, the negative square root for both y 2 and y 3 are used to derive both Z 2 and Z 3 in Equations (25) and 28, respectively. All of this is shown in Equations (31)- (34).…”
Section: S 51 Calculationmentioning
confidence: 99%
“…22 Some authors have also found that BPDs can be used for unequal output power splitting where, several techniques were reported in the literature to address this issue for 3-way BPD and 5-way BPD. [23][24][25][26][27] The main objective of this article is to investigate seven-way BPD with an arbitrary output power splitting for the first time. It would be of a special interest to extend the number of BPD output ports according to applications of these dividers in wireless communication systems, antenna feeders, radars, and RF amplifiers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the value of the fixed characteristic impedance that guarantees input port matching in the latter methodology is subject to parametric analysis. To overcome such a drawback, a systematic detailed design of unequal-split 3-way BPDs with uniform TLs was proposed in [27], where the characteristic impedances can be accurately obtained using analytically derived equations.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, general equations are derived to design 3-way unequal split BPDs with arbitrary TLs parameters (i.e. the electrical lengths of the TLs between the divider ports are not fixed as in [25], and the characteristic impedances are not the same for all TLs as in [27]). The derived equations show that the other two methods are special cases of the proposed one.…”
Section: Introductionmentioning
confidence: 99%